Development of CL184 human monoclonal antibody combination for rabies post-exposure prophylaxis, from preclinical design to clinical evaluation - Marissen, W. E.; Niezgoda, M.; Ellison, J.; Franka, R.; Kuzmina, N.; Kusmin, I.; Taylor, T.; Rupprecht, C. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
The currently recommended prophylaxis for individuals exposed to rabies virus is the combined administration of rabies vaccine and rabies immune globulin (RIG). However, limited supply hampers the availability of RIG, particularly in enzootic areas. To circumvent the global RIG limitation we aimed to develop a human monoclonal antibody combination, CL184, for rabies post-exposure prophylaxis (PEP) that would replace the plasma origin RIG. CL184 consists of two human IgG1 mAbs, CR57 and CR4098, which are directed against non-overlapping rabies virus (RV) glycoprotein epitopes. Previously, we have shown that the in vitro breadth of neutralization of CL184 against a large panel of street RV of various animal origins as well as in vivo protection by CL184 in a Syrian hamster rabies challenge model was comparable to results obtained with human RIG. A detailed preclinical selection procedure was applied to establish the CL184 antibody combination. Efforts on RV surveillance to ensure adequate coverage by CL184 continue. In addition, encouraging data from the Phase I (US and India) and Phase II (US and Philippines) clinical evaluation of CL184 have been obtained. In preparation of the pivotal Phase III evaluations for CL184, a final Phase IIb evaluation has been executed for which data analysis is ongoing. The future availability of CL184 may help to ensure consistent supply of pivotal life-saving biologics to rabies endemic areas and could substantially contribute to the reduction of human rabies deaths, when combined with educational measures and efforts to eliminate canine rabies.